Specific inflammatory cytokines regulate the expression of human monocyte 15-lipoxygenase. - Conrad, D J (1992)
Arachidonate 15-lipoxygenase (arachidonate:oxygen 15-oxidoreductase, EC 1.13.11.33) is a lipid-peroxidating enzyme that is implicated in oxidizing low density lipoprotein to its atherogenic form. Monocyte/macrophage 15-lipoxygenase is present in human atherosclerotic lesions. To pursue a basis for induction of the enzyme, which is not present in blood monocytes, the ability of relevant cytokines to regulate its expression was investigated. Interleukin 4 (IL-4), among 16 factors tested, specifically induced 15-lipoxygenase mRNA and protein in cultured human monocytes. Interferon gamma and hydrocortisone inhibited this induction. High-performance liquid chromatography analysis of lipid extracts from IL-4-treated monocytes detected 15-lipoxygenase products esterified to the cellular membrane lipids, indicating enzymatic action on endogenous substrates. Stimulation of IL-4-treated monocytes with calcium ionophore or opsonized zymosan A enhanced the formation of 15-lipoxygenase products. These data identify IL-4 and interferon gamma as physiological regulators of lipoxygenase expression and suggest an important link between 15-lipoxygenase function and the immune/inflammatory response in atherosclerosis as well as other diseases.